(untitled) (MAUSAM, 2001)
The Soil-Plant-Atmosphere- Water (SPA W) model has been calibrated and validated using field experiment data from 1991-92 to 1993-94 for wheat crop at Varanasi district. Long-term (1973-74 to 1995-96) daily weather data were combined with general observation of wheat growth and soils to provide daily water budgets for 23 years. The model was calibrated with one year detailed crop growth characteristics and soil water observations and validated with another year soil water observations. The daily-integrated water stress index (WSI) values at the end of crop season correlated quite well with observed grain yield in this region. The water budget analysis shows a distinct optimum sowing period from 5th to 25th November and an optimum sowing date on 15th November with minimal water stress index. These results demonstrate the potential of SPA W model for planning irrigation scheduling and water management for wheat crop in this region.